OPTIMASI JALUR PERJALANAN ANTARA JAKARTA DAN SURABAYA MENGGUNAKAN ALGORITMA DIJKSTRA: Optimizing Travel Routes Between Jakarta and Surabaya Using the Dijkstra Algorithm - Rahmadi, Deddy; Putri, Tarisha Najwa; Ilmi, Derrida Atsmarotul; Rohmah, Sinta Miftakhul; Safinka, Dela Nuraini (Yayasan Al-Amin Qalbu, 2025)
The Dijkstra algorithm is a popular method for determining the shortest path in a positively weighted graph and is widely used in various applications such as navigation systems and computer networks. This study analyzes the effectiveness of the Dijkstra algorithm in finding the shortest route between cities in Indonesia, using an example application between Jakarta and Surabaya. Each city is represented as a node and each road as an edge in the graph, with distance or travel time as the weight. The implementation is carried out in Python, using secondary data comprising 20 cities. The results indicate that the Dijkstra algorithm is capable of determining the shortest path between two cities, with the shortest distance found being 664.08 km between Jakarta and Surabaya. This study highlights the importance of optimizing the Dijkstra algorithm for greater efficiency in large networks, as well as its broad applications for improving efficiency in various fields, including transportation and computer networks.